Case report: Cerebellar atrophy associated with phenytoin intoxication in a town in the Amazon region (Research, Society and Development, 2023)
Cerebellar ataxia is one of the classic symptoms of cerebellar atrophy, also considered one of the main lesions that affect motor coordination, being irreversible and interfering in the performance of movements, which are uncertain, unsafe, uncoordinated and imprecise, thus weakening the motor frame of the patient. This cerebellar injury can be caused by high doses associated with the chronic use of Phenytoin, a drug that belongs to the hydantoin class, a sodium channel blocker, metabolized by hepatic CYP2C9/10, it is one of the first-choice antiepileptics for treatment/management of epilepsy. This report highlights the case of a patient who presented difficulty in walking and consequently worsened motor coordination, gingival hyperplasia and hirsutism. After investigation through laboratory and imaging tests, phenytoin intoxication was confirmed due to its chronic use and cerebellar atrophy developing gait ataxia.